Design and Preparation for the Saemaul Undong Model Village Project in Africa - 허장 (한국농촌경제연구원, 2009)
Supported by the African Development Bank, and mediated by the Secretariat Office of the Korea-Africa Economic Cooperation, the Korea Rural Economic Institute has conducted a feasibility study to assess a proposed project to introduce a rural development strategy, known as Saemaul Undong, in the Democratic Republic of Congo. The overall objective of this study is to prepare a baseline methodology and elaborate the implementation plan necessary for validation and submission of the project to the KOAFEC Secretariat. Three villages, Kinseki II and Mbungu-Menga in Kasangulu Territory, and Kinsedi in Madimba Territory, are selected by the Korean Saemaul Undong Center, an organization which will be supposedly agent to manage the project in D. R. Congo. Those villages are located near the capital city, Kinshasa, showing the typical socio-economic and cultural features of rural countryside. Their main income source comes from charcoal production utilizing nearby bushes and forest, thereby causing deterioration of environment. Main crop cultivated has been manioc, which is only for the purpose of self-supply, not for sale, due to the insufficiency to sell at the market. The housing condition in the village is not suitable for human residence. The floors are bare ground on the same height as outside ground. The average educational level in the village is less than secondary. They do not have any access to a health clinic. There are some drinking water sources in each village, although mostly people must walk about 1 km carrying water jars around three times a day. In all the three villages that were surveyed, villagers gave priority to the production of manioc and maize. Virtually all farming work was done manually using simple farm tools such as hoes and sickles. Agriculture was totally rain-fed, resulting in high risk of crop failure in times of unfavorable weather. Poverty in the villages is an urgent matter that should not be neglected any longer. No other governmental development projects are underway only just for the areas. Local officers promised to provide any necessary administrative help for the project. For the last four or five years, a local NGO, named “D.R. Congo Saemaul Undong Center” has initiated the SMU project in the Bas-Congo Province, supported by the Korea International Cooperation Agency. The CSUC’s performance has been well known to the areas in which this project is supposed to start. The organization will be the best implementation agency for this project considering its experiences in the SMU project in neighboring villages. Korean Saemaul Undong Center had suggested project continuing for three years, and total cost is estimated to be $290,250 for D. R. Congo. Each project item, construction of “my own farm,” public well for drinking water, brick houses with rain collectors, products selling stands, multi-purpose truck, communal laundry and bathing facilities, public toilet, animal bank, agricultural product storage, sewerage and electrical facilities, and Saemaul factory. The projects of building public wells and laundry and bathing facilities have to be excluded because of its expected amount of costs. Some items, such as the brick houses project with rain collectors, toilets, and a community hall for meeting and storage, as well as my farm project, and providing a truck have to be implemented during the first year since the first priority should be focused on the basic needs of the villagers and income generation. For measuring the achievements of the project, indicators are suggested for the following five criteria: relevance, effectiveness, efficiency, impact, and sustain-ability. Comparing the project with other similar ones under implementation in African countries, “Millennium Villages Project” by Millennium Promise, UNDP, and the Earth Institute of Columbia University was selected. Korea International Cooperation Agency, ST-EP Foundation, and Gyeongsangbuk-do Province of Korea decided to support financially the MVP implementing in Uganda and Tanzania labeling it as “Korean Millennium Villages Project.” The KMVP will have some difficulty in applying and practicing the experiences of Korean rural and agricultural development in general, and Saemaul Undong in particular, because the MP regards the Korean side as one of donors. Another issue is that the size of the target villages in MVP is too large?the population of a village is assumed to be as many as five thousand. Villages with a big population tend to hamper close relationship and contacts among themselves, and weaken the driving force for the project.